Bi-component polyurethane adhesive composition as well as preparation method and application thereof
By using a chain extender system of multifunctional hydrogen-containing compounds and liquid polybutadiene glycol in two-component polyurethane adhesives and a viscosity adjustment system of hydrogenated castor oil and polyamide wax powder, the problem of insufficient permeability and hydrolysis resistance of existing adhesives in water treatment components is solved, and efficient bonding and long-term service life are achieved.
Patent Information
- Application Number
- CN202510000181.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In the application of existing two-component polyurethane adhesives in water treatment components, there are problems such as poor permeability, insufficient hydrolysis resistance and acid and alkali resistance, resulting in poor bonding effect and short service life.
A chain extender system consisting of multifunctional hydrogen-containing compounds and liquid polybutadiene glycol is adopted, and a viscosity adjustment system composed of hydrogenated castor oil and polyamide wax micropowder is combined to improve the permeability and hydrolysis resistance of two-component polyurethane adhesives.
It achieves ideal bonding strength and long-term service life in water treatment components, has good hydrolysis and acid and alkali resistance, and the viscosity adjustment system can provide thixotropy without significantly increasing the flow viscosity.
Smart Images

Figure BDA0005224722760000021 
Figure BDA0005224722760000101 
Figure BDA0005224722760000111
Abstract
Description
Technical Field
[0001] The invention relates to a two-component polyurethane adhesive composition and a preparation method thereof, and application of the two-component polyurethane adhesive composition in bonding and sealing materials of water treatment components. Background Art
[0002] Two-component polyurethane adhesive is a commonly used adhesive for filtering reverse osmosis membranes. Performance requirements include good chemical resistance, good permeability to the membrane, and no bubble formation during filtration and washing of the filter element. Generally, during the preparation of the membrane element, the high permeability of the adhesive to the membrane can cause less foaming problems during the use of the membrane element. At the same time, as an adhesive for reverse osmosis membranes, it should have a specific and appropriate viscosity, which can penetrate and spread at an appropriate speed on the membrane surface: if the viscosity of the adhesive is too low, it tends to spread horizontally, and capillary phenomena or rise through the membrane pores at the glue application site, resulting in gaps in certain parts of the membrane leaf surface due to insufficient glue application, and the ideal sealing effect cannot be achieved; if the viscosity of the adhesive composition is too high, there is insufficient surface penetration in the membrane leaf, and there is a clear interface transition, resulting in poor bonding. The adhesive also needs to have a suitable open time to allow the adhesive to penetrate and pass through the membrane before curing to achieve a good seal. In addition, since reverse osmosis membrane adhesives are in a complex water environment of sewage or acidic and alkaline cleaning fluids for a long time, in order to ensure a long service life of the membrane components, the membrane component adhesives are required to have strong hydrolysis resistance and acid and alkali resistance.
[0003] CN107073402A discloses a method for preparing a spiral wound filter module using a curable adhesive composition, wherein the adhesive composition uses a two-component adhesive system prepared by Michael addition reaction, which is characterized by difficult control of curing speed, poor wettability, and poor acid and alkali resistance compared to a polyurethane adhesive composition system. CN102850989A discloses a two-component polyurethane adhesive and a preparation method thereof, since such adhesive products use hydrophobically modified fumed silica, and the hydrophobically modified segments use organic polysiloxane, wherein free or dissociated polysiloxane molecules have a potential impact on the service life of the adhesive layer. CN112770830A discloses a polyol composition of a two-component polyurethane adhesive for adhesive films, wherein hydrogenated castor oil or its derivatives are used as an adhesive for reverse osmosis membrane components to increase viscosity and provide thixotropic properties, but the thixotropy provided by hydrogenated castor oil as a thixotropic agent is greatly affected by temperature, and the viscosity properties of the adhesive are easily changed by changes in ambient temperature.
[0004] Therefore, developing a two-component polyurethane adhesive composition that can have good bonding performance in the application of bonding sealing materials of water treatment components is a problem that still needs to be solved in the field. Summary of the invention
[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a two-component polyurethane adhesive composition, which improves the permeability and hydrolysis resistance of the two-component polyurethane adhesive by means of a chain extender system composed of a multifunctional hydrogen-containing compound and liquid polybutadiene diol and a viscosity adjustment system composed of hydrogenated castor oil and polyamide wax micropowder, thereby obtaining a relatively ideal bonding strength and long service life in the application of water treatment components.
[0006] The present invention also aims to provide a method for preparing the two-component polyurethane adhesive composition.
[0007] Another object of the present invention is to provide an application of the above-mentioned two-component polyurethane adhesive composition in the field of water treatment components. The adhesive has the advantages of hydrolysis resistance, acid and alkali resistance, good wettability, high bonding strength, etc., and is particularly suitable for the bonding of wound reverse osmosis membranes and the sealing of hollow fiber filters.
[0008] To achieve the above object, the present invention adopts the following scheme:
[0009] The present invention provides a two-component polyurethane adhesive composition, comprising component A and component B;
[0010] The A component, with its total mass as 100%, comprises the following raw materials by mass percentage:
[0011]
[0012] The B component is a polyurethane prepolymer prepared by the reaction of a polyisocyanate compound and a polyhydroxy compound.
[0013] In the adhesive composition of the present invention, the mass ratio of component A to component B is (0.7-1.2):1, preferably (0.9-1.1):1, for example, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, etc.
[0014] In the adhesive composition of the present invention, the mass ratio of the multifunctional hydrogen-containing compound in component A to the liquid polybutadiene diol is 1:(1-3), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3, etc., and the two constitute the chain extender system of the composition; the mass ratio of the hydrogenated castor oil to the polyamide wax powder is (1-5):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, etc., and the two constitute the viscosity adjustment system of the composition.
[0015] In the adhesive composition of the present invention, the castor oil in component A is unmodified refined castor oil, preferably the castor oil has a water content of less than 800ppm, such as 800ppm, 600ppm, 400ppm, 200ppm, 100ppm, 50ppm, etc., and more preferably, the castor oil has a water content of less than 400ppm. Castor oil molecules contain secondary hydroxyl groups, which are introduced into the polyurethane adhesive. The fatty chains connected to the secondary hydroxyl groups can protect the carbamate bonds from being attacked by water molecules, thereby obtaining more excellent hydrolysis resistance, and having better hydrophobicity and hydrolysis stability; at the same time, castor oil has good fluidity due to its appropriate molecular weight, which is beneficial to the adhesive sizing process.
[0016] In the adhesive composition of the present invention, the multifunctional hydrogen-containing compound of component A is a hydrogen-containing compound with an average functionality of >2, such as 2.1, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, etc., preferably >2 and ≤6, more preferably 2.5-3.5;
[0017] The multifunctional hydrogen-containing compound of component A refers to a multifunctional compound containing active hydrogen reactive groups, such as a polyhydroxy compound, which can be a single hydrogen-containing compound or a combination of hydrogen-containing compounds;
[0018] Preferably, the multifunctional hydrogen-containing compound is a mixture of difunctional and more than difunctional hydrogen-containing compounds; it has the functions of both a chain extender and a cross-linking agent, wherein the chain extender is generally a hydrogen-containing compound with a functionality of 2, and the cross-linking agent is a hydrogen-containing compound with a functionality greater than 2;
[0019] The difunctional hydrogen-containing compound is a dihydric primary alcohol containing an aliphatic branch, selected from at least one of 2-ethyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,5-octanediol, 2-methyl-1,4-butanediol, and 2-ethyl-1,3-hexanediol, preferably pentanediol containing an aliphatic branch, such as 2-ethyl-1,5-pentanediol and 2,4-diethyl-1,5-pentanediol;
[0020] The multifunctional hydrogen-containing compound with a functionality greater than two is a hydrogen-containing polyol or polyamine compound, and its average functionality is 2-6, such as 2, 3, 4, 5, 6, etc., preferably 2.5-3.5; in order to increase the degree of crosslinking and improve the hydrolysis resistance of the composition, the multifunctional hydrogen-containing compound with a functionality greater than two preferably has a symmetrical structure; preferably, the multifunctional hydrogen-containing compound with a functionality greater than two as a crosslinking agent is selected from at least one of pentaerythritol, trimethylolpropane, sorbitol, xylitol, glycerol, tetrahydroxypropylethylenediamine, trimethylolpropane ethoxylate, and di(trimethylol)propane, and more preferably at least one of tetrahydroxypropylethylenediamine and di(trimethylol)propane.
[0021] The multifunctional hydrogen-containing compound and liquid polybutadiene diol described in component A react with the polyurethane prepolymer described in component B to form a strong urethane bond. At the same time, a steric hindrance with long and short chains coexisting is established for the urethane bond, forming a hydrophobic protective barrier, reducing the possibility of degradation and decomposition due to long-term corrosion by acid and alkali aqueous solutions. In particular, when the multifunctional hydrogen-containing compound has characteristics such as aliphatic side chains and a symmetrical structure, the hydrolysis resistance is more excellent.
[0022] In the adhesive composition of the present invention, the liquid polybutadiene diol in component A has a molecular weight in the range of 200-2000, such as 200, 500, 1000, 1500, 2000, etc., preferably 300-1200, more preferably 300-600; preferably, the liquid polybutadiene diol is a hydroxyl-terminated liquid polybutadiene.
[0023] The liquid polybutadiene diol in component A has good compatibility with the system. At the same time, the liquid polybutadiene diol is a liquid telechelic polymer. After reacting with the polyurethane prepolymer in component B, it can generate a compound with a three-dimensional network structure, and work together with the multifunctional hydrogen-containing compound to form a spatial protection of the inner and outer layers of the urethane bond. The existence of this structure helps to enhance the hydrolysis resistance, acid and alkali resistance and aging resistance of the adhesive system.
[0024] Further, the liquid polybutadiene diol contains 0-70wt% of diol obtained by copolymerization of butadiene with other monomers, based on the total mass of the liquid polybutadiene diol, for example, 0wt%, 0.1wt%, 1wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, etc.; the liquid polybutadiene diol of component A can be a diol (HTPB) obtained by self-polymerization of butadiene monomer, or can contain a diol obtained by copolymerization of butadiene with other monomers, and the introduction of the copolymerized monomer helps to further improve the mechanical, water resistance and temperature resistance of the adhesive layer;
[0025] Preferably, the diol obtained by copolymerization of butadiene with other monomers is selected from diols obtained by copolymerization of butadiene with at least one of propylene, acrylic acid, isobutylene, 1,4-pentadiene and isoprene, such as butadiene-acrylic acid copolymer diol and butadiene-pentadiene copolymer diol.
[0026] In the adhesive composition of the present invention, the hydrogenated castor oil in component A refers to hydrogenated castor oil, for example, castor oil can be obtained by catalytic hydrogenation under the action of a metal catalyst, and the unsaturated fatty acids therein are reduced to saturated fatty acids. Hydrogenated castor oil is an existing product in the field, and the present invention has no special requirements for its source. The hydroxyl groups on the fatty acid chains of hydrogenated castor oil can swell and gel, and the swollen particles produce weak hydrogen bonds due to the polar groups in the hydrogenated castor oil molecules, forming a thixotropic network structure.
[0027] In the adhesive composition of the present invention, the polyamide wax powder of component A is a powder particle of polyamide wax, which is usually obtained by directly pulverizing a solid wax product or atomizing and cooling a molten liquid wax. It is an existing product in the field, and the present invention has no special requirements for its source; the particle size of the polyamide wax powder is ≤10 microns, such as 10 microns, 8 microns, 6 microns, 4 microns, 2 microns, etc., preferably ≤7 microns;
[0028] Preferably, the molecular weight of the polyamide wax powder is 400-3000, such as 400, 1000, 1500, 2000, 2500, 3000, etc., preferably 500-2000, more preferably 700-900;
[0029] Preferably, the polyamide wax powder is selected from the product prepared by the reaction of hydroxy fatty acid, caprolactam and diamine; more preferably, the hydroxy fatty acid is selected from at least one of hydroxyvaleric acid, hydroxyheptanoic acid, erucic acid, ricinoleic acid, hydroxyoctanoic acid, hydroxynonanoic acid, hydrogenated ricinoleic acid (also known as 12-hydroxystearic acid), 9,10-dihydroxystearic acid, etc.; the diamine is a fatty diamine, selected from at least one of 1,3-propylenediamine, 1.4-butylenediamine, 1,6-hexanediamine, 1,10-decanediamine, dodecyldiamine, etc.;
[0030] More preferably, the polyamide wax powder is selected from the product prepared by the reaction of hydrogenated ricinoleic acid, caprolactam and 1,6-hexamethylenediamine, such as NEW-0421.
[0031] The polyamide wax and hydrogenated castor oil used in the present invention have similar chain segments and group structures, and cooperate with hydrogenated castor oil to form more stretched chain segments, obtain a more complete interpenetrating hydrogen bond system, and enhance the thixotropic effect. Since the combination of polyamide wax and hydrogenated castor oil contains abundant hydroxyl groups and amide groups, the combination of the two can form a strong intermolecular hydrogen bond force, and the non-polar chain in the polyamide wax and hydrogenated castor oil are intertwined to form a network structure. When subjected to external stress, the network structure is broken into single independent units. When the external stress or shear force disappears, the molecules re-form an intertwined network structure. At the same time, the combination of polyamide wax and hydrogenated castor oil also solves the problem of low solubility of polyamide wax in general systems. The synergistic use of hydrogenated castor oil, a relatively small amount and a relatively low viscosity can achieve a good thixotropic effect, and help inter-membrane penetration, which can improve bonding and reduce the possibility of defects in the bonding interface. At the same time, the interaction between the two makes it easier to add and avoids the migration of non-reactants and the temperature sensitivity of the adhesive, which helps the adhesive maintain good bonding strength without attenuation, and achieves the purpose of improving the acid-base medium resistance of the adhesive system.
[0032] From the perspective of the interaction between the adhesive and the bonding substrate, the hydrogenated castor oil and the polyamide wax structure have good interaction and compatibility with the polyester support layer, the polysulfone layer, and the polyamide reverse osmosis functional layer, which helps to enhance the adhesion between the adhesive and the reverse osmosis membrane and improve the water resistance, and maintain the life of the adhesive layer for a long time. In addition, in the adhesive system, the use of hydrogenated castor oil can improve the thixotropy of the adhesive system, but the use of hydrogenated castor oil alone will cause the transparency and viscosity of the system to be more susceptible to temperature. Surprisingly, in the system of the present invention, due to the effect of the selected polyamide wax powder, the temperature-sensitive effect caused by hydrogenated castor oil is almost non-existent. The thixotropy provided by the combination of hydrogenated castor oil and polyamide wax is less dependent on temperature, is insensitive to seasonal and environmental requirements, and is conducive to the stability of the adhesive.
[0033] In the adhesive composition of the present invention, the defoaming agent and filler in component A can be selected conventionally in the field. In some specific examples of the present invention, the defoaming agent and filler can be selected in the following ranges:
[0034] The degassing agent is selected from organic polymers, preferably at least one of organosilicon polymers, high carbon alcohol fatty acid esters, and polyoxyethylene polyoxypropanolamine ethers. The degassing agent helps to accelerate the migration of bubbles present in the glue to the liquid surface and promote the removal of bubbles during the degassing stage of the glue before sizing. The optional brands on the market include at least one of TEGO Airex 920, BYK A 530, etc.
[0035] The filler is selected from ultrafine molecular sieves, preferably 3A molecular sieves;
[0036] Preferably, the average particle size of the filler is 3-20 microns, such as 3 microns, 6 microns, 9 microns, 12 microns, 15 microns, 18 microns, 20 microns, etc., more preferably 5-7 microns. Due to the porous nature of the molecular sieve, the molecular sieve reduces the possibility of bubbles generated in the glue during use while removing moisture, making the glue more uniform and reducing product defects.
[0037] In the adhesive composition of the present invention, the polyisocyanate compound of component B is at least one selected from aliphatic, alicyclic and aromatic difunctional or multifunctional isocyanates, preferably 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 4,4'-dicyclohexylmethane diisocyanate, 1,4-tetraphenyl diisocyanate, 1,6-hexamethylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, more preferably at least one of 4,4'-MDI and 2,4'-MDI;
[0038] Further, the polyisocyanate-based compound optionally contains 0-20wt% of carbodiimide and / or uretonimine-modified polyisocyanate, based on the total mass of the polyisocyanate-based compound, for example, containing 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt% or the like of carbodiimide and / or uretonimine-modified polyisocyanate.
[0039] In the adhesive composition of the present invention, the polyhydroxy compound in component B is a polyol compound, preferably a polymer polyol, such as a polyether polyol or a polyester polyol;
[0040] Preferably, the polyol is at least one of polyoxypropylene polyol and castor oil;
[0041] Preferably, the molecular weight of the polyhydroxy compound is 500-2500, such as 500, 1000, 1500, 2000, 2500, etc., preferably 500-1500;
[0042] Preferably, the functionality of the polyhydroxy compound is 2-3, such as 2, 2.5, 3, etc.
[0043] In the adhesive composition of the present invention, the mass proportion of the polyisocyanate compound in component B is 45-70%, such as 45%, 50%, 55%, 60%, 65%, 70%, etc., preferably 58-63%, based on the total mass of component B.
[0044] In the adhesive composition of the present invention, in the polyurethane prepolymer of component B, the isocyanate group (NCO) accounts for 10-20% of the total mass, such as 10%, 12%, 14%, 16%, 18%, 20%, etc., preferably 13-17%.
[0045] The adhesive composition of the present invention may also optionally include other additives, such as catalysts, wetting agents, defoaming agents, inorganic fillers, antistatic agents, etc., which are conventionally selected in the field, and the present invention does not specifically limit their types.
[0046] The second aspect of the present invention provides a method for preparing the above-mentioned two-component polyurethane adhesive composition.
[0047] Specifically, the two-component polyurethane adhesive composition of the present invention can be obtained by the following preparation method, which comprises the following steps:
[0048] (1) Preparation of component A: Castor oil, a multifunctional hydrogen-containing compound, and liquid polybutadiene glycol are mixed uniformly, and the temperature is raised to 60-70° C., for example, 60° C., 62° C., 64° C., 66° C., 68° C., 70° C., etc., hydrogenated castor oil, polyamide wax micropowder, a defoaming agent, and a filler are added and mixed uniformly, and the temperature is lowered to 30-40° C., for example, 30° C., 32° C., 34° C., 36° C., 38° C., 40° C., etc., and vacuum degassing is performed to obtain component A;
[0049] (2) Preparation of component B: Mix the polyisocyanate compound and the polyhydroxy compound evenly, and react at 70-85°C, for example, 70°C, 73°C, 76°C, 80°C, 83°C, 85°C, etc. for 2-5h, for example, 2h, 3h, 4h, 5h, etc., to obtain a polyurethane prepolymer, i.e., component B.
[0050] In the present invention, when the castor oil, the multifunctional hydrogen-containing compound and the liquid polybutadiene glycol are mixed in step (1), the stirring speed is 2-30 rpm, for example, 2 rpm, 10 rpm, 20 rpm, 30 rpm, etc., and the stirring time is 30-90 min, for example, 30 min, 50 min, 70 min, 90 min, etc.;
[0051] After adding hydrogenated castor oil, polyamide wax powder, defoaming agent and filler, wait until the solid matter is basically soaked by the liquid raw material, and then continue stirring for 1.5-2h, for example, 1.5h, 1.7h, 1.9h, 2h, etc.
[0052] In the present invention, the vacuum degassing in step (1) has a vacuum degree lower than 1500Pa, such as 1400Pa, 1200Pa, 1000Pa, 800Pa, etc. The degassing time is determined according to the volume of the kettle until no bubbles escape from the surface.
[0053] In the present invention, in step (1), for the convenience of adding, hydrogenated castor oil and polyamide wax powder can be premixed in a certain proportion in castor oil to obtain a viscous liquid or paste.
[0054] In the present invention, the polyisocyanate compound is added at a constant temperature of 40-50°C in step (2), such as 40°C, 45°C, 50°C, etc.
[0055] When the two-component polyurethane adhesive composition of the present invention is used, the separately prepared component A and component B are uniformly mixed in a certain ratio, glued or potted and bonded on the surface of the substrate, and cured to prepare a component;
[0056] Preferably, the mixture obtained by mixing component A and component B has a non-flowing time (i.e., operable time) of 30-60 minutes, preferably 40-50 minutes, and a curing completion time of 20-30 hours.
[0057] The third aspect of the present invention provides the use of the above two-component polyurethane adhesive composition in the field of water treatment components, and is particularly suitable for bonding and sealing of windable reverse osmosis membrane components and hollow fiber potting components.
[0058] Compared with the prior art, the two-component polyurethane adhesive composition of the present invention has the following beneficial effects:
[0059] The present invention uses castor oil as a matrix raw material and combines a multifunctional hydrogen-containing compound, liquid polybutadiene glycol, hydrogenated castor oil and polyamide wax micropowder in component A to achieve the purpose of making the material after the adhesive is cured have better hydrolysis resistance and acid and alkali resistance, reduce the failure risk of the adhesive as a seal or bonding adhesive for reverse osmosis membrane components, and improve the service life and reliability.
[0060] In the preferred embodiment of the present invention, when the adhesive composition uses liquid polybutadiene diol, dihydric primary alcohol containing aliphatic side chains, and a multifunctional alcohol cross-linking agent with a symmetrical structure to form a hydrogen-containing compound system, the hydroxyl group and the structural steric hindrance react with the isocyanate to form an adhesive system with a certain cross-linking density and a high reaction strength under the protection of the inner and outer network, so that the adhesive product has excellent water resistance and acid and alkali resistance. In particular, when the liquid polybutadiene diol introduces the diol obtained by copolymerization of butadiene and other monomers, its copolymer structure helps to further improve the mechanical, water resistance and temperature resistance of the adhesive layer.
[0061] The present invention adopts polyamide wax and hydrogenated castor oil to replace the use of fumed silica, and provides thixotropy without significantly increasing the flow viscosity. The relatively low viscosity helps to improve the wetting of the adhesive liquid at the interface of the substrate, and can achieve the possibility of improving bonding and reducing the defects of the bonding interface. At the same time, since the adhesive composition of the present invention does not use fumed silica as a thixotropy modifier, the introduction of organic polysiloxane compounds is avoided, and the decrease or separation of the interlayer bonding strength between the adhesive layer or interface caused by the migration of polysiloxane during the long-term use of the product is eliminated, thereby improving the bonding strength. DETAILED DESCRIPTION
[0062] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0063] The sources of the main raw materials in the examples and comparative examples of the present invention are as follows. Other sources are obtained from common commercial channels unless otherwise specified:
[0064] Refined castor oil: moisture content <400ppm, hydroxyl value 160mgKOH / g, acid value <3mgKOH / g, functionality 3, purchased from Huanyu Oils and Fats;
[0065] Hydrogenated castor oil: white to light yellow powder, hydroxyl value 150-165 mgKOH / g, iodine value ≤ 5, melting point 85-88°C, purchased from Huanyu Oils and Fats;
[0066] Liquid polybutadiene glycol 1: molecular weight 470-530, colorless or light yellow liquid, purchased from MacLean reagent;
[0067] Liquid polybutadiene diol 2: molecular weight 500-800, containing 55 wt% of diol obtained by copolymerization of butadiene and isoprene, based on the total mass of the liquid polybutadiene diol; prepared by the following method:
[0068] ① Using butyl lithium as a catalyst, 2,2-ditetrahydrofuran ether as a polarity regulator, and toluene as a solvent, butadiene and isoprene monomers are ionically polymerized to obtain a copolymer; ② Using m-chloroperbenzoic acid for oxidation to obtain epoxidized polybutadiene-isoprene; ③ Using periodic acid for further oxidation to obtain a terminal aldehyde copolymer; ④ Using sodium borohydride for reduction to obtain a terminal hydroxyl copolymer. By controlling the epoxidation rate, the molecular weight of the copolymer product can be controlled;
[0069] Multifunctional hydrogen-containing compound 1: 2,4-diethyl-1,5-pentanediol, functionality 2, liquid, purchased from Aladdin Reagent;
[0070] Multifunctional hydrogen-containing compound 2: di(trimethylol)propane, functionality 4, purchased from Aladdin reagent;
[0071] Fumed silica: Aerosil R805, polydimethylsiloxane-modified fumed silica, purchased from Evonik;
[0072] Polyamide wax powder: NEW-0421, average particle size (D50) 5 μm, molecular weight 680, purchased from Nanjing Tianshi New Materials;
[0073] Degassing agent: BYK A535, polymer (siloxane-free), purchased from BYK Chemicals;
[0074] Filler: 3A molecular sieve, average particle size 6 μm, purchased from Shanghai Guangji;
[0075] Isocyanate 1: 4,4-diphenylmethane diisocyanate, purchased from Wanhua Chemical;
[0076] Isocyanate 2: carbodiimide-modified 4,4-diphenylmethane diisocyanate, purchased from Wanhua Chemical;
[0077] Polypropylene oxide glycol: average molecular weight 1000, functionality 2, purchased from Wanhua Chemical.
[0078] Examples and Comparative Examples
[0079] Examples B1-B2
[0080] Preparation of component B
[0081] In a reaction kettle with stirring and temperature control, raw materials are added according to the mass percentage in Table 1 below. The specific steps are: add polypropylene oxide glycol and / or refined castor oil to the reaction kettle, preheat at a constant temperature of 45°C, then add isocyanate 1, react at a constant temperature of 70-85°C for 2-3h, add isocyanate 2, continue to stir and react at a constant temperature for 0.5h, obtain component B polyurethane prepolymer, measure NCO index, cool and discharge.
[0082] Table 1 Ratio of raw materials of component B of Example B1-B2 (mass percentage %)
[0083] B component number B1 B2 Isocyanate 1 48 51 Isocyanate 2 12 12 Polypropylene oxide glycol 22 - Refined castor oil 18 37 NCO content % 15.36 15.65
[0084] Examples A1-A12 and Comparative Examples C1-C2
[0085] Preparation of component A
[0086] The raw materials are added according to the mass percentage of the following Table 2. The specific steps are: at room temperature, the refined castor oil, the multifunctional hydrogen-containing compound, and the liquid polybutadiene glycol are added to the double planetary mixing kettle in sequence, the kettle body is closed, the stirring is turned on, the speed is 2-30rpm, and the mixing is stirred for 30min; the temperature in the kettle is raised to 60-70°C, the kettle cover is opened, and hydrogenated castor oil, polyamide wax powder, defoaming agent, and filler are added in sequence, and the solid matter is basically infiltrated by the liquid raw materials, and the stirring is continued for 1.5-2h; the temperature is lowered to 30-40°C, and the bubbles are removed by vacuum, and the vacuum degree is lower than 1500Pa, until no bubbles escape from the surface, and the material is discharged.
[0087] Table 2 Ratio of raw materials of component A in Examples A1-A12 and Comparative Examples C1-C2 (mass percentage %)
[0088]
[0089]
[0090] Examples 1-13 and Comparative Examples 1-2
[0091] Preparation and application of a two-component polyurethane adhesive composition: Component A and component B are mixed and cured according to the proportions in Table 3:
[0092] Component A and component B were mixed evenly according to the proportions in Table 3 to prepare a certain type of sample or block, and the non-flow time and curing time of the adhesive were tested, and then the mechanical and hardness performance tests were carried out, and the ambient temperature was controlled at 23-25°C and the ambient humidity was 50-75%. The results are shown in Table 4.
[0093] Table 3 Proportions of Component A and Component B in Examples 1-13 and Comparative Examples 1-2
[0094]
[0095]
[0096] Performance Testing
[0097] (1) Stagnant time
[0098] Mix components A and B (mass and 100g) according to the calculated ratio, quickly mix them in a homogenizer at 2000rpm for 1min, then place them on the table and start timing. When the liquid surface of the tilted container no longer flows, the timing is completed, which is the no-flow time.
[0099] (2) Gel curing time
[0100] The time for the curing viscosity to reach 100 Pa.s was measured using a cone and plate viscometer Brookfield CAP2000+.
[0101] (3) Shore A hardness test
[0102] The hardness was tested according to GB / T531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber - Shao A, and the hardness was tested after 24h, 72h and 1 week of curing.
[0103] (4) Thixotropic ratio
[0104] The polyol composition (A) was measured using a rheometer in frequency sweep mode with a shear frequency ranging from 1 s-1 to 50 s-1. The following were calculated: the viscosity of the fluid at 1 s-1 divided by the viscosity of the fluid at 10 s-1 (1 / 10), and the viscosity of the fluid at 2 s-1 divided by the viscosity of the fluid at 20 s-1 (2 / 20). The recorded parameters were thixotropic ratio of 1 / 10 and thixotropic ratio of 2 / 20, respectively.
[0105] (5) Acid resistance test
[0106] Prepare a pH = 1 HCl aqueous solution, solidify the glue to prepare a 75 × 25 × 5mm strip sample, completely immerse it in the prepared HCl solution, and place it at 25 ° C for at least one month. Take it out every 7 days, wipe it clean, and measure the mass change rate of the sample.
[0107] (6) Alkali resistance test
[0108] Prepare a NaOH solution with a pH of 13.5, solidify the glue into a strip sample of 75×25×5 mm, completely immerse it in the prepared NaOH solution, heat it in a constant temperature oven at 50°C, leave it for at least one month, take it out every 7 days, wipe it clean, and measure the mass change rate of the sample.
[0109] (7) Mechanical strength test
[0110] The prepared A / B component adhesives were mixed in proportion to obtain a sample with a thickness of 5 mm. The samples were tested according to the methods of "GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" and "GB / T 529-2008 Determination of tear strength of vulcanized rubber or thermoplastic rubber", and the tensile strength, elongation at break and tear strength indicators were achieved respectively.
[0111] (8) Penetration test
[0112] Place the prepared A / B glue mixture on the surface of the non-woven fabric layer of the reverse osmosis membrane, measure the contact angle and mass reduction of the glue on the membrane surface within a specific time range, and calculate the penetration mass percentage. The test equipment is KRUSSDSA25S contact angle tester.
[0113] (9) Bonding strength
[0114] Use the prepared A / B glue to bond the PVC sheet (length × width × thickness: 20 × 5 × 0.5 mm), the bonding area is 5 × 5 cm2, use a tensile testing machine to clamp the tail end of the PVC sheet, and use the tensile testing machine to stretch and test the strength of the bonding surface.
[0115] Table 4 Comparison of test items and results of two-component polyurethane adhesive composition examples and comparative examples
[0116]
[0117]
[0118] From the data in Table 4, it can be seen that the embodiments of the present invention, especially the selected chain extender / crosslinker type with branched chains and the coordination with polybutadiene glycol, provide higher mechanical and bonding strengths by virtue of the protective effect of the inner and outer layer space and a certain crosslinking density, and at the same time help to reduce the decomposition of the system by acid and alkali media; and when liquid polybutadiene glycol introduces the glycol obtained by copolymerization of butadiene and other monomers, its copolymerization structure helps to further improve the mechanical, water resistance and temperature resistance of the adhesive layer. The use of polyamide wax and hydrogenated castor oil can provide sufficient thixotropy, and due to the presence of self-reactive groups and their own hydrophobic properties, it promotes and improves the acid and alkali hydrolysis resistance of the material, which is better than the traditional non-reactive thixotropic system using only fumed silica. On the other hand, the design of the system, the raw materials used and the related polymers are compatible with the molecules of the reverse osmosis membrane layer, and the adhesive system of the present invention has a higher permeability on the surface of the reverse osmosis membrane, which is manifested as a relatively low contact angle and a higher permeation mass percentage at the same time, so that the expectation of the present invention is verified.
Claims
1. A two-component polyurethane adhesive composition, characterized in that: It includes component A and component B; The A component, with its total mass as 100%, comprises the following raw materials by mass percentage: The B component is a polyurethane prepolymer prepared by the reaction of a polyisocyanate compound and a polyhydroxy compound.
2. The two-component polyurethane adhesive composition according to claim 1, characterized in that: The mass ratio of component A to component B is (0.7-1.2):1, preferably (0.9-1.1):1; and / or The mass ratio of the multifunctional hydrogen-containing compound to the liquid polybutadiene glycol is 1:(1-3); and / or The mass ratio of the hydrogenated castor oil to the polyamide wax powder is (1-5):
1.
3. The two-component polyurethane adhesive composition according to claim 1 or 2, characterized in that: The multifunctional hydrogen-containing compound is a hydrogen-containing compound having an average functionality of >2, preferably >2 and ≤6, more preferably 2.5-3.5; Preferably, the multifunctional hydrogen-containing compound is a mixture of a difunctional hydrogen-containing compound and a hydrogen-containing compound having a function greater than difunctional; More preferably, the difunctional hydrogen-containing compound is a primary diol containing an aliphatic branch, selected from at least one of 2-ethyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,5-octanediol, 2-methyl-1,4-butanediol and 2-ethyl-1,3-hexanediol, preferably pentanediol containing an aliphatic branch. Such as 2-ethyl-1,5-pentanediol and 2,4-diethyl-1,5-pentanediol; the polyfunctional hydrogen-containing compound having a functionality greater than two is a hydrogen-containing polyol or polyamine compound, and its average functionality is 2 to 6, preferably 2.5 to 3.5; preferably, the polyfunctional hydrogen-containing compound having a functionality greater than two is selected from at least one of pentaerythritol, trimethylolpropane, sorbitol, xylitol, glycerol, tetrahydroxypropylethylenediamine, trimethylolpropane ethoxylate and di(trimethylol)propane, and more preferably is at least one of tetrahydroxypropylethylenediamine and di(trimethylol)propane; and / or The liquid polybutadiene diol has a molecular weight range of 200-2000, preferably 300-1200, and more preferably 300-600; preferably, the liquid polybutadiene diol is a hydroxyl-terminated liquid polybutadiene; Preferably, the liquid polybutadiene diol comprises 0-70 wt % of diol obtained by copolymerization of butadiene and other monomers, based on the total mass of the liquid polybutadiene diol; More preferably, the diol obtained by copolymerization of butadiene with other monomers is selected from the diol obtained by copolymerization of butadiene with at least one of propylene, acrylic acid, isobutylene, 1,4-pentadiene and isoprene, such as butadiene / acrylic acid copolymer diol and butadiene / 1,4-pentadiene copolymer diol.
4. The two-component polyurethane adhesive composition according to any one of claims 1 to 3, characterized in that: The castor oil has a moisture content of less than 800 ppm, preferably less than 400 ppm; and / or The polyamide wax powder has a particle size of ≤10 microns, preferably ≤7 microns; Preferably, the molecular weight of the polyamide wax powder is 400-3000, preferably 500-2000, more preferably 700-900.
5. The two-component polyurethane adhesive composition according to any one of claims 1 to 4, characterized in that: The defoaming agent is selected from organic polymers, preferably at least one of silicone polymers, higher alcohol fatty acid esters, and polyoxyethylene polyoxypropanolamine ethers; and / or The filler is selected from ultrafine molecular sieves, preferably 3A molecular sieves; Preferably, the average particle size of the filler is 3-20 microns, more preferably 5-7 microns.
6. The two-component polyurethane adhesive composition according to any one of claims 1 to 5, characterized in that: The polyisocyanate compound is at least one selected from aliphatic, alicyclic and aromatic difunctional or multifunctional isocyanates, preferably at least one of 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-tetraphenyl diisocyanate, 1,6-hexamethylene diisocyanate, 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, more preferably at least one of 4,4'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate; and / or The polyisocyanate-based compound optionally comprises 0-20 wt % of a carbodiimide and / or uretonimine-modified polyisocyanate, based on the total mass of the polyisocyanate-based compound; and / or The polyhydroxy compound is a polyol compound, preferably a polymeric polyol; Preferably, the polyol is at least one of polyoxypropylene polyol and castor oil; Preferably, the molecular weight of the polyol is 500-2500, preferably 500-1500; Preferably, the functionality of the polyol is 2-3.
7. The two-component polyurethane adhesive composition according to any one of claims 1 to 6, characterized in that: The mass proportion of the polyisocyanate compound in component B is 45-70%, preferably 58-63%, based on the total mass of component B; and / or In the polyurethane prepolymer of component B, the isocyanate group (NCO) accounts for 10-20% of the total mass, preferably 13-17%.
8. A method for preparing the two-component polyurethane adhesive composition according to any one of claims 1 to 7, characterized in that the steps include: (1) Preparation of component A: Castor oil, multifunctional hydrogen-containing compound, and liquid polybutadiene glycol are mixed uniformly, heated to 60-70° C., hydrogenated castor oil, polyamide wax powder, defoaming agent, and filler are added and mixed uniformly, cooled to 30-40° C., and vacuum defoamed to obtain component A; (2) Preparation of component B: The polyisocyanate compound and the polyhydroxy compound are mixed evenly and reacted at 70-85° C. for 2-5 hours to obtain a polyurethane prepolymer, i.e., component B.
9. The method for preparing the two-component polyurethane adhesive composition according to claim 8, characterized in that: When mixing castor oil, multifunctional hydrogen-containing compound and liquid polybutadiene glycol in step (1), the stirring speed is 2-30 rpm and the stirring time is 30-90 min; After adding hydrogenated castor oil, polyamide wax powder, defoaming agent and filler, continue stirring for 1.5-2 hours until the solid material is basically soaked by the liquid raw material; and / or The vacuum degassing in step (1) has a vacuum degree lower than 1500 Pa; and / or The polyisocyanate compound is added at a constant temperature of 40-50°C in step (2).
10. The use of the two-component polyurethane adhesive composition according to any one of claims 1 to 7 or the two-component polyurethane adhesive composition prepared by the method according to claim 8 or 9 in the field of water treatment components, especially suitable for bonding and sealing of windable filter membrane components and hollow fiber ultrafiltration treatment components.
Citation Information
Patent Citations
Two-component polyurethane adhesive and preparation method thereof
CN102850989A
Method of making spiral wound filtration modules with a curable adhesive composition and modules made thereby
CN107073402A
Double-component polyurethane adhesive for preventing chimney from being corroded and method for preparing double-component polyurethane adhesive
CN103087668A
Polyurethane adhesives for reverse osmosis modules
CN107847878A
Hydrogenated natural oils to thicken the polyol component of a two-component polyurethane adhesive for bonding membranes
CN112770830A
Cited By
Joint filling glue material without sagging on vertical surface and preparation method thereof
CN121160277A